Stress–strain behavior of marine calcareous soil-tire mixtures. Issue 6 (3rd June 2022) - Shariatmadari, Nader; Norouzi, Mohsen; Rezvani, Reza
Abstract: The increase in the volume of scrap tires has led to environmental concerns in different locations of the world, particularly in the coastlines. Managing this solid waste, including reuse in civil engineering applications (e.g. geotechnical projects) can be an effective solution to solve the problem. A series of drained triaxial tests was performed on Qeshm calcareous soil obtained from Qeshm Island. Specimens were prepared at loose and dense relative densities and mixed with different percentages of tire crumbs (TCs), including 0%, 10%, 20%, 30%, and 50%. The variation ratio parameter was introduced to evaluate the effect of TCs on the engineering properties of the soil-tire mixture. Based on the results, the stress–strain behavior of the calcareous soil was strongly influenced by TCs contents. As the tire content (TC) increases, the stress transfer mechanism changes from particle-particle to tire-tire, which results in a shear strength reduction. For an example, the addition of 50% of TCs to the calcareous soil resulted in a 64% reduction in the maximum deviatoric stress under a confining pressure of 600 kPa. In addition, the secant modulus at maximum deviatoric strength of the soil-tire mixture with 50% of TCs decreased about 80%.